Towards Geothermal Reservoir Characterization and Monitoring Through Seismic (Ambient Noise) and Geodetic (INSAR) Imaging: Torfajökull Volcano and Reykjanes Peninsula, Iceland. - Martins, Joana E. (author); Hooper, A.J. (author); Hanssen, R.F. (author) (2021)
After decades of oil, gas, and coal exploitation, we have learned about some of the unpleasant aftereffects of subsurface resource exploration. Adverse long-term impacts, some known during exploration periods, others only afterwards, may include induced seismicity, land subsidence, or even sinkholes. While geothermal is currently seen as a sustainable source of energy, seismicity induced by inappropriate operational procedures or lack of knowledge of the subsurface may incite doubt and public sensitivity about its future use. A problem frequently posed before and during geothermal exploration is the cost of geophysical measurements for resource assessment, subsurface characterization during the prospection phase, and monitoring accompanying production. In this study, we investigate and discuss the potential of two economic geophysical measurement techniques for geothermal reservoir characterization and monitoring: passive seismic interferometry for better subsurface characterization through seismic imaging (static model), and satellite-based radar interferometry for geodetic imaging (dynamic model). Seismic imaging using passive seismic techniques allows for subsurface characterization via Ambient Noise Tomography, and supports the assessment of geothermal resources without requiring the use of shooting, which reduces the cost compared to active seismics. Geodetic imaging, by measuring the surface displacements during and after production, allows for the monitoring of the effects of production and constrains reservoir modelling, and can be achieved through the use of (freely available) satellite imagery. We discuss the results of both techniques over two high enthalpy geothermal sites in Iceland: Reykjanes Peninsula and Torfajökull volcano. While the Reykjanes Peninsula has geothermal fields that have been producing for decades, Torfajökull’s geothermal field, despite being the largest in Iceland, is not producing. For the subsurface characterization, we use S-wave velocity tomographic images derived from ...